The Impact of Business Synergy and Digital Orientation on University Performance - Bima Septian Hafidzayanto; Siti Chamidah; Yusup Arif (Journal La Sociale, 2026)
This study aims to analyze the influence of business synergy and digital orientation on university performance. Ninety respondents from various universities were selected using purposive sampling. Data were analyzed using Smart PLS software to test the structural model and relationships between variables. The results indicate that business synergy significantly influences university performance, while digital orientation does not. These findings highlight that improving university performance in the digital era depends on the institution's ability to develop digital capabilities and implement them effectively in a structured manner. The main limitations of this study lie in the relatively small sample size and the use of cross-sectional data. Future research is recommended to expand the sample size and employ a longitudinal approach to obtain more comprehensive results.